FREEQUENCY OF F S SP PO ON NT TA AN NE EO OU US S B BA AC CT TE ER RI IA AL L P PE ER RI IT TO ON NI IT TI IS S ( (S SB BP P) ) I IN N C CI IR RR RH HO OT TI IC C P PA AT TI IE EN NT TS S W WI IT TH H A AS SC CI IT TE ES S D - Ali Saaqqiib (Journal of University Medical & Dental College, 2012)
A AB BS ST TR RA AC CT T O Ob bj je ec ct ti iv ve es s: : The frequency of Spontaneous Bacterial Peritonitis (SBP) in cirrhotic patients with ascites due to hepatitis C and B viruses Materials and methods: This study was conducted in Medical Unit of Madina Teaching Hospital, Faisalabad from January, 2011 to June, 2011. A total of 100 patients were studied. Patients, who were either already diagnosed or had symptoms and signs of chronic liver disease were included in the study. The main tool for the diagnosis of SBP was diagnostic peritoneal paracentesis. Results The overall frequency of Spontaneous Bacterial Peritonitis in cirrhotic patients with ascites due to HCV and HBV was 31 in 100 patients (31%). 43 males and 57 females were studied. Among 31 patients with SBP, there were 13 males and 18 females. Conclusion: SBP is a common complication of liver cirrhosis leading to significant morbidity and mortality. The classical sign of SBP like fever and abdominal pain may not be present. We concluded from our study that cirrhosis complicated by SBP is becoming more prevalent and most of the people are unaware of the disease till very late and health education should be imparted in order to create awareness about the disease and its outcome.